PENGATURAN JALUR PENERBANGAN KEPULAUAN RIAU OLEH SINGAPURA - Ruth Suryani Sijabat; Ahmad Jamaan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Airspace is an important territory for a country. Airspace that has economic opportunities is often a target for foreign parties. The Indonesian region has a strategic geographical location from sea, land to air. Its strategic location makes Indonesia have to protect its territory strictly. This research will focus on Indonesian airspace in the Kepulauan Riau, Indonesian airspace controlled by Singaporean authorities since 1946 by explaining the early history of Singapore's control and Indonesia's condition at that time. The author uses a constructivism perspective to be able to answer this research question, this perspective believes that international politics is formed as a result of persuasive thinking. The author analyzes at the level of analysis of the nation state based on the theory of national interests. This study uses qualitative research methods by analyzing sources related to this issue. This research shows that control over the Kepulauan Riau airspace managed by the Singaporean authorities has been going on for decades due to Indonesia's inability to manage the area due to the location of the airspace which has high use value but requires good technology and human resources. Mastery of Singapore has a positive impact on both the country by realizing its military, economic and political interests. Keywords: FIR, national interest, technology